Review of morphometric measurements used in anuran species descriptions and recommendations for a standardized approach - Watters, Jessa L.; Cummings, Sean T.; Flanagan, Rachel L.; Siler, Cameron D. (Zootaxa, 2016)
Standardization and repeatability is at the heart of all scientific research, yet very little literature exists to standardize morphometric measurements within vertebrate groups. This is particularly true for amphibians. Our study attempts to rectify this lack of methodological standardization for the measurement of morphological characters in anurans through an extensive literature survey of 136 species descriptions representing 45 currently recognized families of frogs. The survey revealed 42 morphological measurements represented in five percent or more of the literature reviewed. All measurements are listed by most commonly used name, acronym, and most precise definition, and we provide statistics summarizing the variation in measurement use and description from the surveyed literature. Of these 42 measurements, a subset of 16 were found in the top 75% of all surveyed descriptions and identified as a focal set of recommended measurements in an effort to standardize the morphometric measurements that describe anuran species diversity. Illustrations of these 16 measurements are provided as a visual reference for standardizing their measurement.